2006
DOI: 10.1063/1.2208167
|View full text |Cite
|
Sign up to set email alerts
|

Microwave plasma in hydrocarbon liquids

Abstract: The generation of microwave plasma in liquid with vapor bubbles has been achieved and will soon be applied to high-speed chemical vapor deposition. Vapor bubbles are induced from an electrode by heating. The deposition rate of diamondlike carbon films depends on the pressure and the power of the microwave supply. Polycrystalline silicon carbide is synthesized on a silicon substrate in a mixture of n-dodecane and silicone oil. The dispersion of water droplets in liquid creates many pores on the silicon carbide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 18 publications
0
44
0
Order By: Relevance
“…[37][38][39] The temperature of the inner electrode at plasma ignition was measured by inserting a thermocouple into the inner electrode and it was concluded that the plasma is generated when the temperature of the electrode reaches the saturation temperature of the liquid. 12 This result indicates that there is a relationship between the ignition temperature and the saturated temperature.…”
Section: ͑4͒mentioning
confidence: 68%
See 4 more Smart Citations
“…[37][38][39] The temperature of the inner electrode at plasma ignition was measured by inserting a thermocouple into the inner electrode and it was concluded that the plasma is generated when the temperature of the electrode reaches the saturation temperature of the liquid. 12 This result indicates that there is a relationship between the ignition temperature and the saturated temperature.…”
Section: ͑4͒mentioning
confidence: 68%
“…It has been reported from experiments on amorphous-carbon deposition in a hydrocarbon liquid, that the deposition rate is found to be approximately 9000 times faster than that for typical chemical vapor deposition in gases. 12 The MW plasma generated in an organic liquid has been researched in our previous studies. [12][13][14][15] Plasma is generated by supplying MW radiation of 200 to 400 W at the tip of a submerged electrode similar to a monopole antenna widely used for conventional gaseous plasma.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations